Some findings on the marine diesel using gas condensate fuels - Бабаев, Гаджи Мирза оглы (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents a comparative analysis of the main physical and chemical characteristics of various fuels, including mixtures of heavy diesel fuel and gas condensate. It reveals the findings of comparative experiments on the marine 2CH10.5/13 auxiliary diesel engine using the above-mentioned fuels. The research showed that mixtures of gas condensate (GC) with the boiling (heating) start point not less than 120 0С and furnace fuel oil (М) with the flash-point not less than 1300С meet the requirement of the Maritime Register and can be used in marine diesels if the concentrate ratio makes up 15.0 % GC + 85.0 % М. The use of the devised mixture (15.0 % GC + 85.0 % М) in marine internal combustion engines would increase diesel fuel resource and reduce the environment pollution.